2021
DOI: 10.1016/j.healun.2021.07.026
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 messenger RNA vaccine antibody response and reactogenicity in heart and lung transplant recipients

Abstract: Background: While several studies have observed that solid organ transplant recipients experience diminished antibody responses to SARS-CoV-2 mRNA vaccination, data specific to heart and lung transplant (HT/LT) recipients remains sparse. Methods: US adult HT and LT recipients completed their vaccine series between January 7 and April 10, 2021. Reactogencity and SARS-CoV-2 anti-spike antibody were assessed after a priming dose (D1) and booster dose (D2). Modified Poisson regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 29 publications
(26 reference statements)
8
74
2
1
Order By: Relevance
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Solid organ transplant-specific treatments (calcineurin inhibitors, antimetabolites, corticosteroids) were often associated with a higher non-response rate or lower antibody titres [ 20 , 21 , 24 , 40 , 56 , 62 , 65 , 69 , 72 , 75 , 81 , 136 , [138] , [139] , [140] , [141] , [142] , 144 , 145 , 148 , [154] , [155] , [156] , [157] , 159 , 160 ] ( Table S5 ). Older age and lower estimated glomerular filtration rate were repeatedly associated with a non-responder status [ 21 , 24 , 79 , 120 , 138 , 142 , 144 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that COVID-19 vaccines have reduced immunogenicity in immunosuppressed individuals compared with immunocompetent individuals. [5][6][7][8] In the limited epidemiological research thus far, the approved vaccines appear to be less effective in immunosuppressed individuals relative to the general population. [9][10][11] However, these studies were all limited by either small sample size, individuals with a specific condition, a single vaccine or a short study period before the Delta variant became dominant and booster dose approved.…”
Section: Introductionmentioning
confidence: 99%
“…Since approval, the vaccines have been highly effective at preventing SARS-CoV-2 infection and severe illness,4 but there is still limited evidence regarding vaccine effectiveness in immunosuppressed individuals. Studies have shown that COVID-19 vaccines have reduced immunogenicity in immunosuppressed individuals compared with immunocompetent individuals 5–8. In the limited epidemiological research thus far, the approved vaccines appear to be less effective in immunosuppressed individuals relative to the general population 9–11.…”
Section: Introductionmentioning
confidence: 99%